Structure based biophysical characterization of the PROPPIN Atg18 shows Atg18 oligomerization upon membrane binding - Scacioc, A; Schmidt, C; Hofmann, T; Urlaub, H; Kühnel, K; Pérez-Lara, Á (Nature Research, 2018)
PROPPINs (β-propellers that bind polyphosphoinositides) are PtdIns3P and PtdIns(3,5)P2 binding autophagy related proteins. They contain two phosphatidylinositolphosphate (PIP) binding sites and a conserved FRRG motif is essential for PIP binding. Here we present the 2.0 Å resolution crystal structure of the PROPPIN Atg18 from Pichia angusta. We designed cysteine mutants for labelling with the fluorescence dyes to probe the distances of the mutants to the membrane. These measurements support a model for PROPPIN-membrane binding, where the PROPPIN sits in a perpendicular or slightly tilted orientation on the membrane. Stopped-flow measurements suggest that initial PROPPIN-membrane binding is driven by non-specific PIP interactions. The FRRG motif then retains the protein in the membrane by binding two PIP molecules as evident by a lower dissociation rate for Atg18 in comparison with its PIP binding deficient FTTG mutant. We demonstrate that the amine-specific cross-linker Bis(sulfosuccinimidyl)suberate (BS3), which is used for protein-protein cross-linking can also be applied for cross-linking proteins and phosphatidylethanolamine (PE). Cross-linking experiments with liposome bound Atg18 yielded several PE cross-linked peptides. We also observed intermolecular cross-linked peptides, which indicated Atg18 oligomerization. FRET-based stopped-flow measurements revealed that Atg18 rapidly oligomerizes upon membrane binding while it is mainly monomeric in solution.